microRNAs profiling of small extracellular vesicles from midbrain tissue of Parkinson’s disease - Li, Zhengzhe; Chen, Dongdong; Pan, Renjie; Zhong, Yanbiao; Zhong, Tianyu; Jiao, Zhigang (Frontiers in Molecular Neuroscience, 2023)
Small extracellular vesicles (sEVs) are generated by all types of cells during physiological or pathological conditions. There is growing interest in tissue-derived small extracellular vesicles (tdsEVs) because they can be isolated from a single tissue source. Knowing the representation profile of microRNA (miRNA) in midbrain tissue–derived sEVs (bdsEVs) and their roles is imperative for understanding the pathological mechanism and improving the diagnosis and treatment of Parkinson’s disease (PD). bdsEVs from a rat model of PD and a sham group were separated and purified using ultracentrifugation, size-exclusion chromatography (SEC), and ultrafiltration. Then, miRNA profiling of bdsEVs in both groups was performed using next-generation sequencing (NGS). The expression levels of 180 miRNAs exhibited significant differences between the two groups, including 114 upregulated and 66 downregulated genes in bdsEVs of PD rats compared with the sham group (p < 0.05). Targets of the differentially expressed miRNAs were predicted by miRanda and RNAhybrid, and their involvement in the signaling pathways and cellular function has been analyzed through the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO). Furthermore, we explored the expression levels of miR-103-3p, miR-107-3p, miR-219a-2-3p, and miR-379-5p in bdsEVs, sEVs derived from plasma, and plasma of both groups of rats. Interestingly, the expression levels of miR-103-3p, miR-107-3p, miR-219a-2-3p, and miR-379-5p were elevated in bdsEVs and sEVs from plasma; in contrast, their expression levels were decreased in plasma of the rat model of PD. In summary, miRNAs may play a significant role in the onset and development of PD, and miRNAs need to be selected carefully as a research subject for exploring the pathological mechanism and the potential therapeutic targets and diagnostic markers of PD.